การรับรู้ประสบการณ์ด้านจิตใจของพนักงานภายหลังได้รับการปรึกษาเชิงจิตวิทยาแนวพุทธ - กวีไกร ม่วงศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This research described employees’ psychological experiences of their participation in Buddhist Counseling Therapy using Concept mapping, the methodological approach combining qualitative and quantitative strategies. The purpose of the study was to understand how employees give meaning to and construct their experiences on their perception. Eight clients, who had received Buddhist counseling was selected by purposive sampling. Two sessions of data-gathering were conducted by depth-interview and card-sorting for qualitative and Multidimensional scaling (MDS) analysis procedure, respectively. Nine thematic clusters were identified: (1) Counselor Facilitation, (2) Perception of Counseling Atmospheres, (3) Confidence in Counseling, (4) Problem Awareness, (5) Introspection in Problem Solving Process, (6) Results of Counseling Process, (7) Mental State Enhancing Elements, (8) Living Harmoniously with Others, and (9) Perceived Benefits of Counseling. The study enhanced the understanding of Thai employees’ experiences of Buddhist Counseling Therapy and can be utilized as resources for the Buddhist counselors who might collaborate with Thai employees.